Aerodynamic conditions of comfort and environmental human security in a modern building of towns and cities - Аксьонов, О.О.; Ударцева, Т.Є. (Proceedings of National Aviation University (archive), 2009)
Analytical review article on ecological secyrity of modern urban constructions and effect of airdynamical indeces of air on pedestrians. It was found out that wind blows are most dangerous for pedestrians under conditions of modern multistoried buildings. At was shown that objectius data on atmosphere wind effect on construction ecology could be obtained only in airdynamic pipes of special design. The summary provides the main objectives that could be achieved with the help of airdynamic pipes.